IMPLEMENTASI SMART ENVIRONMENT CITY DALAM TATA KELOLA LINGKUNGAN DI KOTA TANGERANG - Adie Dwiyanto Nurlukman; Abdul Basit (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Tangerang City is a city that is one of the capital's supporting areas, which is experiencing severe environmental pollution due to rapid urbanization, industrial activity, the large number of electric vehicles, and low public awareness of the environment. By utilizing technology and innovation to create smarter, more sustainable, and greener cities, the smart city environmental concept can provide effective solutions to environmental problems. Smart city is a concept that is applied globally, including in the city of Tangerang, Indonesia. The combination of technological developments with urban infrastructure is an effort to improve citizens' quality of life, increase the effectiveness of public services, and encourage sustainable economic growth. There is significant research development regarding the application of smart environment cities, including innovation in government, but there is still very little research regarding the application of smart environment cities and efforts to increase environmental sustainability. This study emphasizes the importance of the government's role, especially in policies, to mitigate the negative impact of urban development in Tangerang City on the environment.